PEMBIASAAN KEGIATAN-KEGIATAN KEAGAMAAN DALAM PEMBENTUKAN KARAKTER DISIPLIN DI SMPI KARANGPLOSO - Eka Wahyu Sri Wilujeng; Anwar Sa’dullah; Dzulfikar Rodafi (Vicratina : Jurnal Ilmiah Keagamaan, 2020)
From the research conducted obtained research results in order to answer the focus of existing research, namely: (1) The process of religious activities that are more than one, namely: (a) reading yasin before starting teaching and learning activities every morning, (b) Duha prayer is obliged to congregate at rest, (c) Dhuhr prayer is obligatory in congregation, (d) there is a BTQ (Read Write the Qur'an), (e) reading istighosah every Friday morning before the teaching and learning activities begin, and (f) PHBI (Islamic Holidays Celebration). (2) There are two indicators of discipline in the implementation of religious activities are: (a) Many students are enthusiastic about participating in religious activities, (b) Students have high attention to the rules, and discipline that has been arranged by the school. (3) There are several forms of discipline in Karangploso Middle School, the first: (a) Guidebook, this book has a function as a condition for the final semester exam, and is reported to parents with the aim of knowing how the development of their children's attitudes at school , (b) Punishment or punishment is important in the form of discipline, because by giving punishment students can understand what is good and right.